2022
DOI: 10.1155/2022/5409323
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Propofol Intravenous Anesthesia on Serum NGF, S100B Protein, and Immune Function in Patients with Bladder Cancer after Resection

Abstract: Objective. To explore the efficacy of intravenous propofol anesthesia on patients with bladder cancer after resection, as well as its effect on cognitive and immune function. Methods. Patients with bladder cancer and received resection of bladder cancer at our hospital from May 1, 2019, to November 30, 2021, were retrospectively retrieved and included in this study. The included patients were summarized into group A (isoflurane) and group B (intravenous propofol). The anesthesia intervention effect, serum NGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Among the LFPI rats, we also found that high 2d‐S100B plasma levels also correlated with better neuromotor functional recovery. Among the peri‐operative factors, recent isoflurane anesthesia, as used in our study, may result in low plasma S100B levels in rabbits 3d after embolic stroke, 53 as well as in patients who underwent bladder cancer resection surgery 54 . The effects of isoflurane on plasma pTAU‐Thr 231 are unknown.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Among the LFPI rats, we also found that high 2d‐S100B plasma levels also correlated with better neuromotor functional recovery. Among the peri‐operative factors, recent isoflurane anesthesia, as used in our study, may result in low plasma S100B levels in rabbits 3d after embolic stroke, 53 as well as in patients who underwent bladder cancer resection surgery 54 . The effects of isoflurane on plasma pTAU‐Thr 231 are unknown.…”
Section: Discussionmentioning
confidence: 79%
“…Among the peri-operative factors, recent isoflurane anesthesia, as used in our study, may result in low plasma S100B levels in rabbits 3d after embolic stroke, 53 as well as in patients who underwent bladder cancer resection surgery. 54 The effects of isoflurane on plasma pTAU-Thr 231 are unknown. Craniotomy may also produce mild pathologies in the brain, 55 as also shown here by the mild impairment of neuroscores F I G U R E 3 Effects of early post-LFPI seizures and LEV upon protein biomarkers in LFPI rats.…”
Section: Discussionmentioning
confidence: 99%
“…17 Several mechanisms by which propofol specifically exerts antitumor effects on bladder cancer have also been presented. [6][7][8][9][10] In addition, meta-analyses indicate a survival benefit with propofol-based anesthesia for various cancers. [18][19][20][21] Please note that the 5-yr survival rates were calculated using the Kaplan-Meier approach, adjusting for the patients that were censored during follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…The designation "quality register," which is necessary to obtain government funding, is given to both registries (Supplemental Digital Content 1, https://links.lww.com/ ALN/D487). The data analysis and statistical plan used for a similar study on breast cancer, 10 which was written and filed at https://regionvastmanland.se/vardgivare/forskning-och-utbildning/forskning/ in February 2020, was used for this study as well. A similar propensity score approach was implemented but with different clinical variables and sensitivity analysis corresponding to bladder cancer subtypes and outcomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation